Engineering the electronic structure and transport coefficients of Janus MoSSe monolayer by applying z-axial strain. (2021) - Singh Khosa, Gurpal; Kumar, Ranjan; Gupta, Shuchi
Highlights: Numerical determination of the electronic structure and transport properties of the Janus MoSSe monolayer under z-axial strain. Janus MoSSe monolyer shown to be dynamically stable; and a direct 1.63 eV band gap semiconductor; under z-axial strain transition to indirect band gap. Application of z-axial strain enhances the tpower factor of n-type Janus MoSSe monolayer. Abstract: By performing the Density functional theory based first principle calculations, we investigate the effect of z-axial (compressive and tensile) strain on the electronic band structure and transport coefficients of Janus MoSSe monolayer. The unstrained Janus MoSSe monolayer is a direct band gap semiconductor having an energy gap of 1.63 eV. The electronic band structure is very sensitive to the application of z-axial strain. Because of which the electronic transport coefficients get modulated. We found out that z-axial tensile strain enhances the power factor of n-type Janus MoSSe monolayer, however no enhancement is predicted for p-type Janus MoSSe monolayer